CDK4/6 inhibition enhances pulmonary inflammatory infiltration in bleomycin-induced lung fibrosis - Anna Birnhuber; Bakytbek Egemnazarov; Valentina Biasin; Ehsan Bonyadi Rad; Malgorzata Wygrecka; Horst Olschewski; Grazyna Kwapiszewska; Leigh M. Marsh (Respiratory Research, 2020)
Abstract Inhibitors of cyclin-dependent kinases 4/6 (CDK4/6) block cell cycle progression and are commonly used for treatment of several forms of cancer. Due to their anti-proliferative mode of action, we hypothesized that palbociclib could attenuate the development of bleomycin-induced lung fibrosis. In a preclinical setting, mice were treated with bleomycin and then co-treated with or without palbociclib. Lung function, collagen deposition and pulmonary inflammation were analysed after 14 days. Bleomycin treatment led to an increase of pulmonary fibrosis and inflammation, and concomitant decline of lung function. Palbociclib treatment significantly decreased collagen deposition in the lung after bleomycin treatment, but did not ameliorate lung function. Importantly, palbociclib augmented inflammatory cell recruitment (including macrophages and T cells) in the bronchoalveolar lavage fluid. This study supports the recent alert from the Food and Drug Administration (FDA) that use of CDK4/6 inhibitors, such as palbociclib, may have severe pulmonary adverse effects. Our study showing heightened pulmonary inflammation following palbociclib treatment highlights the risk of severe inflammatory adverse effects in the lung. This is of special interest in patients with known pulmonary risk factors and emphasizes the need of careful monitoring all patients treated with CDK4/6 inhibitors for signs of lung inflammation.